Respuesta :
Answer:
(x + 2)(x² - 2x + 4)
Step-by-step explanation:
x³ + 8 ← is a sum of cubes, which factors in general as
• a³ + b³ = (a + b)(a² - ab + b²)
x³ = (x)³ ⇒ a = x and 8 = 2³ ⇒ b = 2
x³ + 8 = (x + 2)(x² - 2x + 4) ← in factored form
Answer:
[tex]x^{3} +8=(x+2)(x^{2} -2x+4)[/tex]
Step-by-step explanation:
The binomial can be factored by the binomial form by trinomial. This binomial is a sum of cubes, whose general form presents the following result.
[tex](x^{3} +y^{3} )=(x+y)(x^{2} -xy+y^{2} )[/tex]
Substituting the values of x and y we will have
[tex]x^{3} =x^{3} ; y^{3} =8[/tex]
Obtaining the cubic roots of each variable
[tex]x=x; y=2[/tex]
So
[tex]x^{3} +8=(x+2)(x^{2} -2x+4)[/tex]